2007
DOI: 10.4269/ajtmh.2007.76.830
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bed Net Use in the Gambia: Implications for Malaria Control

Abstract: Malaria is still one of the biggest health threats in the developing world, with an estimated 300 million episodes per year and one million deaths, most of which are in sub-Saharan Africa. Although the efficacy and cost-effectiveness of treated bed nets has been widely reported, little is known about the range, strength, or interaction between different factors that influence their demand at the household level. This study modeled the determinants of bed net ownership as well as the factors that influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 46 publications
7
48
4
1
Order By: Relevance
“…At the individual level, factors influencing net use have been reported to include age and gender [5,7-10], education, occupation/livelihood [11-13], degree of control over household decision-making [14], malaria knowledge, beliefs and risk perceptions [5,15-21], perceived benefits and disadvantages of nets [5,17,18,21], trust in health workers providing health education and LLINs [22], knowledge of appropriate net use/care practices, and net-hanging skills [23-25]. Household level determinants of net use include household size and composition [14], the number of children under five years of age (U5) in the household, intra-household sleeping arrangements [5,13,26], household structure and space [5,7,9,18,26,27], household decision-making processes and power structures [14], and use of other vector control measures [14,19,28].…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, factors influencing net use have been reported to include age and gender [5,7-10], education, occupation/livelihood [11-13], degree of control over household decision-making [14], malaria knowledge, beliefs and risk perceptions [5,15-21], perceived benefits and disadvantages of nets [5,17,18,21], trust in health workers providing health education and LLINs [22], knowledge of appropriate net use/care practices, and net-hanging skills [23-25]. Household level determinants of net use include household size and composition [14], the number of children under five years of age (U5) in the household, intra-household sleeping arrangements [5,13,26], household structure and space [5,7,9,18,26,27], household decision-making processes and power structures [14], and use of other vector control measures [14,19,28].…”
Section: Introductionmentioning
confidence: 99%
“…Although distribution of ITNs to pregnant mothers and under 5 year-olds has been massively expanded in Tanzania, there is little information on the frequency of ownership, knowledge, attitudes and practices (KAP) of pregnant women on ITNs use. Some studies have suggested that mosquitoes nuisance, malaria knowledge and socio-demographic factors, including education and household income are important determinants of bed net ownership and use (Opiyo et al, 2007, Wiseman et al, 2007, Mazigo et al, 2010. However, knowledge on the benefits of ITNs or ownership of ITNs does not necessarily imply use.…”
Section: Introductionmentioning
confidence: 99%
“…On the demand side, financial constraints are the main reasons given by households for not acquiring health products (Guyatt et al 2002;Bates et al 2004aBates et al , 2004bWiseman et al 2007;Eisele et al 2009;Afolabi et al 2009;Krezanoski et al 2010). Indeed, demand for these products appears quite price elastic.…”
Section: Demand and Supply Chainmentioning
confidence: 99%